Group Technology for Optimizing Manufacturing Facility Layout - Nguyen Van Thanh; Nguyen Thai Nguyet Thanh; Nguyen Viet Tinh (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2021)
In recent years, the process of cellular manufacturing and group technology have received a lot of attention and popularity in many developed countries. By applying Group Technology (GT), many benefits of flow-line production can be attained in a batch production system. GT improves material handling significantly by reducing material flow time, distance, and setup times. In this paper, an earnest investigative attempt was made to provide valuable information regarding the use of Group Technology by applying to a real world jobshop system. The proposed GT model has the flexibility of choosing the number of cells required, which is very useful in examining different manufacturing cell configurations; or in case the workshop or factory prefers a certain number of work cells. The GT model results were found satisfactory and superior to other techniques in some cases.